Skin-directed therapy and biologic response modifiers in mycosis fungoides - Vieri Grandi; Virginia Alba Colantuono; Nicola Pimpinelli (PAGEPress Publications, 2024)
The most common and widespread type of cutaneous T-cell lymphoma is mycosis fungoides (MF), and it has a multiphasic clinical and biological course, with early stages being indolent for many years and later stages being faster and more aggressive. The clinical stage has a significant impact on the management and course of treatment: in the early stages, skin-directed therapies (SDT) plus/or biologic response modifiers (BRM); in the later stages, radiotherapy and/or systemic therapies. Even though national and international societies and groups periodically update their clinical recommendations, there is still no universally accepted approach. This paper reviews and discusses the various SDT and BRM options, either separately or in combination.